2016
DOI: 10.1002/we.2017
|View full text |Cite|
|
Sign up to set email alerts
|

A new k‐epsilon model consistent with Monin–Obukhov similarity theory

Abstract: A new k-ε model is introduced that is consistent with Monin-Obukhov similarity theory (MOST). The proposed k-ε model is compared with another k-ε model that was developed in an attempt to maintain inlet profiles compatible with MOST. It is shown that the previous k-ε model is not consistent with MOST for unstable conditions, while the proposed k-ε model can maintain MOST inlet profiles over distances of 50 km.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 26 publications
0
38
1
Order By: Relevance
“…In simulations, the disk-averaged velocity U disk is calculated by averaging the local velocity in the disk region, then is applied to estimate the upstream reference velocity U ref based on Equations (16) and (17) and the momentum source S u,i based on Equation 15, respectively.…”
Section: Actuator Disk Model Based On Thrust Coefficient (-Ct)mentioning
confidence: 99%
See 2 more Smart Citations
“…In simulations, the disk-averaged velocity U disk is calculated by averaging the local velocity in the disk region, then is applied to estimate the upstream reference velocity U ref based on Equations (16) and (17) and the momentum source S u,i based on Equation 15, respectively.…”
Section: Actuator Disk Model Based On Thrust Coefficient (-Ct)mentioning
confidence: 99%
“…A widely used turbulence model for the thermal stratified boundary layer was developed by Alinot and Masson [15] where a coefficient of the buoyant terms in the ε transport equation is calibrated with atmospheric stability. However, van der Laan et al [16] showed that this model cannot keep the flow homogeneity in a large domain under unstable conditions and thus developed a turbulence model consistent with MOST. In Prospathopoulos et al [13], an additional buoyancy production based on the Richardson number Ri was added to the turbulent kinetic energy equation to model wind turbine wakes under stable conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a diurnal cycle stable conditions are typically seen at night with cooler land temperatures while unstable conditions appear in day times with elevated temperatures. Typically, non-neutral conditions dominate for mean wind speeds lower than 15 m s −1 [1] [2]. Non-neutral conditions are thus present during the most prevalent wind speed conditions experienced by commercial wind farms.…”
Section: Introductionmentioning
confidence: 99%
“…Two k − turbulence model modifications for MOST are investigated: the methods of Alinot and Masson [3] and the recently proposed model from M.P. van der Laan et al [1]. The models are applied to the wind farm location, to understand the model accuracy in complex terrain.…”
Section: Introductionmentioning
confidence: 99%